ESTIMATION OF BENEFIT RESERVES IN ENDOWMENT INSURANCE USING THE INDONESIAN MORTALITY TABLE IV AND ZILLMER METHOD - Sadli, Wanda Hamidah; Sari, Devni Prima (PATTIMURA UNIVERSITY, 2025)
This study focuses on determining the benefit reserves for endowment life insurance using the Zillmer method, an extension of the prospective reserve approach. Benefit reserves are crucial as they represent the funds insurance companies must set aside to cover future claims. Traditionally, reserves can be calculated retrospectively or prospectively. Still, the Zillmer method introduces an innovative approach by incorporating a Zillmer rate and time to account for loading costs, particularly at the beginning of the policy period. This research's novelty lies in applying the Zillmer method using the most recent Indonesian Mortality Table (TMI) IV, which provides updated and accurate life expectancy data for calculating reserves. The study reveals that the reserve values ​​calculated using the Zillmer method are initially lower than those derived from the conventional prospective method due to the inclusion of the Zillmer rate. However, as the policy progresses, the reserve values ​​gradually align with the prospective reserves after the Zillmer time period concludes. This study not only applies the Zillmer method in a local context with updated mortality data but also demonstrates how insurance companies can manage reserves more effectively, particularly in the early years of the policy.